Repair of the (6–4) Photoproduct by DNA Photolyase Requires Two Photons1. Issue 29 (12th June 2013) - Yamamoto, Junpei; Martin, Ryan; Iwai, Shigenori; Plaza, Pascal; Brettel, Klaus
<x xml:space="preserve">Abstract</x> It takes two (photons) to tango: Single‐turnover flash experiments showed that the flavoenzyme (6–4) photolyase uses a successive two‐photon mechanism to repair the UV‐induced T(6–4)T lesion in DNA (see picture). The intermediate (X) formed by the first photoreaction is likely to be the oxetane‐bridged dimer T(ox)T. The enzyme could stabilize the normally short‐lived T(ox)T, allowing repair to be completed by the second photoreaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>